THE EFFECT OF HEALTH EDUCATION ON SELF EFFICACY ON POST STROKE PATIENTS IN BLUD RSU DR. ZAINOEL ABIDIN BANDA ACEH - Roma Sitio; Said Devi Elvin; Nirwan Nirwan (Jurnal Ilmiah Keperawatan, 2020)
Stroke is a cerebrovascular disease the second leading cause of death and the third leading cause of disability. Globally in 2018, 80 million people worldwide have strokes and 50 million survivors of strokes live with permanent disabilities. The percentage of stroke in Aceh in 2018 has reached 103 percent or above the national average of 93.4 percent. The impact of the high percentage of the number of people affected by stroke in Aceh has made the life expectancy of the people of Aceh to be low or only 67.8 years, below the national average of 71.5 years. Stroke has a large impact on physical, psychological and social functioning. Most people with stroke are faced with limitations in physical, psychological and social functions. This condition causes post-stroke depression which affects the inability to take care of themselves (self-care) such as bathing, dressing, toileting and making toilet and shower transfers. The purpose of this study was to determine the effect of psychoeducation-based health education on self-efficacy in post-stroke patients. The design used is quasi experement with control group. The sample in this study were post-stroke patients who went to the BLUD RSU dr. Zainoel Abidin Banda Aceh determined based on power analysis sampling. Data collection instruments in the form of Self Care Assessment Tool for Stroke Patients whose results be analyzed univariately and bivariately. The results showed that there were differences in self efficacy in post-stroke patients for the intervention group between before and after psychoeducation-based health education. Furthermore, it is known that there is no difference in self efficacy in post-stroke patients for the control group between measurement 1 and measurement 2. This study concludes that psychoeducation-based health education has been proven to be effective in increasing self-efficacy in post-stroke patients.